Procalcitonina, marcadores inflamatórios e parâmetros clínicos em pacientes internados com suspeita de sepse - Fernanda Rocha de Freitas (2017)
Sepsis is a set of clinical signs and symptoms resulting from a systemic inflammatory process associated with the presence of an infection. The clinical diagnosis of sepsis is based on the presence of at least two of the following criteria: body temperature above 38°C (fever) or below 36°C (hypothermia), tachycardia, tachypnea, and altered in global leukocyte counts. Several biomarkers are used and / or studied in order to provide an early diagnostic and better clinical management of sepsis. Thus, the present study evaluated the performance of PCT, IL10, inflammatory markers (CRP, global leukocyte and lactate) and clinical parameters in hospitalized patients with suspected sepsis. For this, 61 patients were evaluated, assisted by the sepsis protocol of the Hospital Madre Tereza. The study participants were followed for a period of three days (D0), 24h (D1) and 48h (D2) after) and classified by the clinical staff of the hospital in "sepsis" or "non-sepsis". The results showed that, on the day of opening of the sepsis protocol, the median global leukocyte count (p = 0,003), PCT (p = 0,016), lactate (p = 0,001) and IL-10 (p = 0,016) were significantly higher in the sepsis group than in the nonsepsis group. On the other hand, the medians of CRP between the groups were not statistically different (p = 0,372). In the D1 group, the medians of IL-10 (p = 0,001) and lactate (p = 0,024) were statistically different between the sepsis and non-sepsis groups, and the medians were higher for the sepsis group. On the last day of follow-up, D2, there was no difference between the medians for most of the markers evaluated in relation to the sepsis and non-sepsis groups, although all presented higher levels for the sepsis group. For PCT and IL-10, there were no significant differences between the three days evaluated and the discharge from hospital or death, but for the lactate the difference between D2-D0 was related to the outcome. Multivariate logistic regression analysis revealed a significant association between the global leukocyte variable and sepsis. Increased levels of PCT, IL-10, Leukocyte Global and Lactate on the day of protocol opening correlated with the presence of sepsis, but only the leukocyte count was independently associated with sepsis. Despite being a well-studied topic, early diagnosis of sepsis remains a challenge due to the absence of an effective biomarker capable of accurately and specifically predicting this clinical condition.